Investigation on the collation of the first Fight book (Leeds, Royal Armouries, Ms I.33) - Binard Fanny; Jaquet Daniel (Acta Periodica Duellatorum, 2016)
This paper investigates the collation of the first Fight Book, the Leeds, Royal Armouries, Ms I.33. It critically reviews previous hypotheses about the composition of the quires and the identification of the material lacuna, and proposes a new hypothesis. This investigation is based on observation of the original after restoration (2012) and the simulation of the previous hypotheses with a working document composed of laminated sheets into which reproductions were inserted. Bifolia were physically attached, forming quires by successive folds. This simulation phase allowed us to analyse textual and pictorial content according to the various postulates and to propose identification of the material lacuna. The pivot point allowing a new argumentation are the two counterfoils of the two flying leaves (fol. 19 and 26), which were not taken into account by previous researchers. Several synoptical diagrams of the representation of the quire are enclosed for the reader to follow the developments.